Protótipo de sistema de automação residencial para o auxílio de pessoas idosas e com dificuldades de locomoção - Morais, Bianca Stephanie Guimarães (Universidade Federal Rural do Semi-Árido, 2018)
others. This is a product developed in prototype application for Android, in practice, in the area of technology and digital adaptation. The objective is to develop and deploy the use of automation in the aid of elderly people with locomotion difficulties, as well as the use of requirements elicitation techniques. Faced with this, implement a prototype for the bluetooth test, as a means of communication between Arduino and Android platforms. Therefore an application for the control of the environment was developed, as the focus on the technological solution. Literature review methods and the development of unified modeling language diagrams were used. The results were satisfactory, considering that the prototype worked in a simple way, but providing its initial functions, being verified in a non-formal way. This does not exist for work needs prior to the prospect needs and needs in the development of the application to the needs of elderly and / or people with locomotion.
Monografia
Keywords: Automação; Dificuldade de locomoção; Idoso; Aplicativo; Arduino; Android; Bluetooth; Automation; Difficulty of locomotion; Old man; Arduino; Bluetooth; App; Android; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA